METODE KONSTRUKSI PEMBANGUNAN DERMAGA WATUSAMPU KECAMATAN ULUJADI KOTA PALU PROVINSI SULAWESI TENGAH DITINJAU DARI SEGI TEKNIS, BIAYA DAN WAKTU - Velda Ramadana, Suhariyanto, Fadjar Purnomo (Prokons: Jurnal Teknik Sipil, 2019)
The 930m2 dock was built to facilitate Watusampu Harbour with easy loading and unloading to the existing harbour. The purpose of the thesis is to compare two alternative construction methods and determine the more effective and efficient technical implementation, cost, and time aspects. The first alternative used a pontoon and the second used a steel construction bridge supporting the construction works to be.The required data were of shop drawings and work unit price of Palu 2016 to plan the construction method, project cost estimate, and schedule of the project. Besides, structural drawings, loading, wind speed, wave of height, sea water speed, and bathymetry map were required to design the bridge structure. In terms of technical implementation the first alternative construction method is more difficult to implement and has a high risk level to cause project financial loss. The review results in 8 months 13 days or 256 workdays using pontoon; effective workdays started from 1 October 2014 to 13 June 2015 at IDR63,204,967,037.71 overall cost; 6 months 21 days or 203 workdays using temporary steel bridge; effectively started on 1 October 2014 to 21 April 2015 at IDR72,979,687,667.90  overall cost.    Keywords: construction method is more effective and efficient, pontoon, steel construction bridge